Development and characterization of magnetic micropumps - Yang, Yueze (2010)
In this report, the novel idea of using a magnetic elastomer by mixing Polyimethylsiloxane (PDMS) with ferrofluid will be investigated. A literature review of various key concepts will be explained to give a clear understanding of the project.